Shuffle the shoemaker - Blyton, Enid; Taylor, Thomas (Award Publications Worksop, England, 2014)
Shuffle the Shoemaker is a children$1 (Bs story about a kind-hearted shoemaker named Shuffle, known for his generosity and craftsmanship. Despite his hard work, Shuffle struggles to make ends meet, but his kindness never falters. One day, magical elves secretly help him by completing his work overnight, crafting beautiful shoes that bring him unexpected success. The story celebrates themes of kindness, gratitude, and the rewards of helping others. Through Shuffle$1 (Bs humility and the elves$1 (Bassistance, the tale teaches the importance of compassion and community.s